2011
DOI: 10.3758/s13414-011-0171-1
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-look effects on temporal discrimination within sound sequences

Abstract: The multiple-look notion holds that the difference limen (DL) decreases with multiple observations. We investigated this notion for temporal discrimination in isochronous sound sequences. In Experiment 1, we established a multiple-look effect when sequences comprised nine standard time intervals (S) followed by an increasing number of comparison time intervals (C), but no multiple-look effect when one trailing C interval was preceded by an increasing number of S intervals. In Experiment 2, we extended the desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
28
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 38 publications
(96 reference statements)
5
28
1
1
Order By: Relevance
“…The relative DL for the target interval (400 ms) was 6.8% in average. This result is consistent with previous reports of perceptual DL for temporal intervals of 400 ms [26], [37]. Previous studies have generated mixed findings with respect to the influence of musical expertise on the sensitivity of individuals to duration manipulation.…”
Section: Discussionsupporting
confidence: 92%
“…The relative DL for the target interval (400 ms) was 6.8% in average. This result is consistent with previous reports of perceptual DL for temporal intervals of 400 ms [26], [37]. Previous studies have generated mixed findings with respect to the influence of musical expertise on the sensitivity of individuals to duration manipulation.…”
Section: Discussionsupporting
confidence: 92%
“…Further work at shallower tempo contours, where model predictions differ most, using sequences of variable length, would aid comparative evaluation of the two models. This may not be trivial to achieve, as tempo contours below 2.5% can be difficult to perceive without a large number of intervals (Friberg and Sundberg, 1995), while the present evidence for the multiple-look model relies on relatively few intervals, with recent work demonstrating significantly diminishing returns for longer sequences (Drake and Botte, 1993;Miller and McAuley, 2005;ten Hoopen et al, 2011).…”
Section: Discussionmentioning
confidence: 75%
“…3, the Weber fraction is higher in the 1-interval condition than in the two other conditions. This is not surprising given that it is known that performance is better when multiple instead of single intervals are presented (see for instance [47][48][49]). However, the results also revealed that in the three conditions under investigation, the Weber fraction is not constant.…”
Section: Recent Data: Restricted Rangementioning
confidence: 95%